Transvestite Holy Women in Early and Proto-Byzantine Christianity - González Palacios, Héctor (My University, 2020)
Transvestite nuns is a really common topic in Byzantine hagiographical literature. The stories of saints like Marina, Matrona of Perge, Anastasia Patrikia or Euphrosyne of Alexandria, among many others, as well as in other situations in hagiographies in which women dress up like men (i.e. in Saint Tarasius Life, when a group of women in disguise to enter the saint's tomb) reflect a common practice during Late Antiquity. Although it has been studied as a peculiar case of Byzantine society or in a Medieval context, I believe that this is the result of a long process about the role of women in society that starts in Classical Greece and Rome and hatchs out with the arrival of the new religions in the Mediterranean, specially Christianity. Dress in Antiquity does not only mean clothes, but identity: dressing as a man suppose the asuming of a maculine role or, at least, a denial of feminity (and what it involves: marriage, children, housekeeping...). Through cross-dressing and the renunciation of sexuality (another of their classical primary functions), these women were able to preach and convert as males, although they were not unanimously seing positively by their peers. Christianity in Late Antiquity and Proto-Byzantine Period allowed women an alternative discourse through asceticism, in which they could assume an asexual masculine role. Asceticism meant a threat, especially in Late Antiquity, to classical patriarchal family, because chastity and its consecutive sanctity became a new element of prestige through which the individual could arise. Christian transvestite Holy Women fought between fame and marginalisation, between the new models that radical forms of Christianity proposed and the classical patriarchal ones that defended other Christian leaders, like Saint Paul or Tertullian.
Les saintes travesties dans le christianisme primitif et proto-byzantin
Keywords: Travestismo; Historia medieval; Hagiografía cristiana; Mujeres en el cristianismo; Cristianismo; Women; Género; Mujeres; Tardoantigüedad